Amplification and expression of c-MET correlate with poor prognosis of patients with gastric cancer and upregulate the expression of PDL1. (8th March 2021) - Yang, Ya'nan; Wang, Chenchen; Dai, Congqi; Liu, Xinyang; Li, Wenhua; Huang, Mingzhu; Zhao, Xiaoying; Ji, Dongmei; Li, Jin; Guo, Weijian
Abstract: The prognostic significance of c-MET in gastric cancer (GC) remains uncertain. In the present study, we examined the amplification, expression, and the prognostic value of c-MET, human epidermal growth factor receptor 2 (HER2), and programmed cell death 1 ligand 1 (PDL1), together with the correlations among them in a large cohort of Chinese samples. A total of 444 patients were included. The immunohistochemistry (IHC) and the dual-color silver in situ hybridization (SISH) were performed to examine their expression and amplification. Univariate and multivariate analyses were performed by the Cox proportional hazard regression model, and survival curves were estimated by the Kaplan–Meier method. The positivity determined by IHC of c-MET was 24.8%, and the MET amplification rate was 2.3%. The positivity rates of HER2 and PDL1 were 8% and 34.7%, respectively. PDL1 expression had a significantly positive association with c-MET expression. c-MET positivity played a significant prognostic role in disease-free survival (DFS) ( P  = 0.032). Patients with mesenchymal-epithelial transition (MET) amplification had significantly poorer prognosis on both DFS and overall survival (OS). Subgroup analysis showed that in HER2-negative patients, but not in HER2-positive patients, MET-positive patients had significantly worse DFS ( P  = 0.000) and OS ( P  = 0.006). c-MET regulated the expression of PDL1 through an AKT-dependent pathway. c-MET inhibitor enhanced the T-cell killing ability and increased the efficacy of PD1 antibody. c-MET was found to be an independent prognostic factor for DFS of GC patients. A combination of c-MET inhibitors and PD1 antibodies could enhance the killing capacity of T cells, providing a preliminary basis for the clinical research on the same combination in GC treatment.